Current smokers’ perception of cigarette graphic health warnings and smoking habits: a cross sectional study from Nepal - Mishra, Shiva Raj; Bhandari, Parash Mani; Marahatta, Sujan Babu; Rana, Hari Krishan Singh; Acharya, Pawan; Khanal, Vishnu (Health Prospect, 2016)
Background: Nepal introduced Tobacco Products (Control and Regulatory) Act in 2011. This act has mandatory provision of enlarged graphical health warning in Nepali language on at least 75% area on the package of all the tobacco products. This study examined the perception of cigarette graphic health warnings and smoking habits among current smokers. Methodology: This is a cross-sectional study conducted in Butwal sub-metropolitan city in Rupandehi district of Nepal. Among 19 wards of the sub-metropolitan city, four wards were selected randomly by computer-generated codes. Enumerators purposively selected 10 shops from each ward, then recruited every third cigarette buyer from each shop to make a total of five. Smoking status was ascertained by asking if they had ever smoked in last thirty days. We approached 200 people, of whom 40 (20.0%) didn’t agree to participate and 10 (5.0%) didn’t smoke currently. Thus, information from 150 current smokers was finally included in the analysis. Results: Nearly 71% of respondents said they would smoke even if the price of cigarette was doubled. Similarly, 55.3% reported that they had intention to quit smoking, followed by 62.0% agreeing on taxation of cigarette and tobacco products is essential. Nearly 81% said it is necessary to keep health warnings in the package of cigarette. About 87% knew that the Government of Nepal has introduced some regulations to control tobacco products. Nearly 80% of respondents had heard of new provision on enlarged graphic health warning on cigarette packages. More than one-fourth (26.7%) had reduced the frequency of smoking since they started using packages with enlarged graphic health warning. Conclusion: Majority had heard of graphic health warning on cigarette packages. Greater than a half of the respondents had intention to quit smoking, and nearly two-third identified taxation as important means to control smoking. A quarter of respondents reported that they forewent smoking after they started using new packages with enlarged graphic health warning. Further research on impact of graphic health warning on smoking levels through repeated cross sectional studies can be the future research priority.